2015
DOI: 10.1155/2015/463640
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of an EPS Concrete Buffer Layer Thickness on Debris Dams Impacted by Massive Stones in the Debris Flow

Abstract: The failure of debris dams impacted by the massive stones in a debris flow represents a difficult design problem. Reasonable materials selection and structural design can effectively improve the resistance impact performance of debris dams. Based on the cushioning properties of expanded polystyrene (EPS) concrete, EPS concrete as a buffer layer poured on the surface of a rigid debris dam was proposed. A three-dimensional numerical calculation model of an EPS concrete buffer layer/rigid debris dam was establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Since M i � _ H i , the rotational motion of a clump can be found by simultaneously solving Equations (4) and (5). e equation for translational motion can be written in the following form:…”
Section: Equations Of Motion For a Clumpmentioning
confidence: 99%
See 1 more Smart Citation
“…Since M i � _ H i , the rotational motion of a clump can be found by simultaneously solving Equations (4) and (5). e equation for translational motion can be written in the following form:…”
Section: Equations Of Motion For a Clumpmentioning
confidence: 99%
“…Over the years, various engineering measures have been used to mitigate or prevent natural granular flow disasters. Common prevention and control measures generally include civil engineering works such as check dams, grid-type dams, lateral walls, deflection and terminal walls, and berms or barriers that control debris flows [4,5]. However, if the prevention and control engineering measures fail due to unreasonable engineering layout or insufficient project argument, they may cause more serious damage and loss [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have shown that there are two effective measures to improve the resistance to impacts and shock waves: thickening the structure layer 1 and developing new materials. 2,3 However, thickening the structure layer is not the best solution, which also increases the cost. Consequently, it is necessary to conduct further research to develop new materials with excellent energy absorbing performance.…”
Section: Introductionmentioning
confidence: 99%
“…Debris flow is a natural process and stopping such a natural phenomenon is impossible; however, mitigation measures can be undertaken to lessen the impact of hazards and human injuries. Traditional ideas consider constructing civil engineering works such as check dams, gridtype dams, lateral walls, deflection and terminal walls, berms or barriers to control debris flows (Van Dine, 1996;Yu et al, 2015), but they are still far from reliable. At present, the management of debris flows is carried out by the processes of blocking, preventing and draining in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the management of debris flows is carried out by the processes of blocking, preventing and draining in many countries. 'Blocking' means building various kinds of check dams in the transportation zone of a channelized debris flow in order to decrease the channel gradient locally, minimise scour along the bottom and sides of the stream steep, intercept solid particles in the debris flow and reduce its destructive power in downstream areas (Van Dine, 1996;Yu et al, 2015;Zhang et al, 2011a); 'Preventing' works consist of collecting wells and drainage pipes, which are the standard method to stabilise slowly moving or intermittently moving landslide masses in debris flow catchments and prevent landslides from transforming into debris flows (Takahashi, 2007;Zhang et al, 2011a); 'Draining' works include impediments to flow, lateral walls and deflection walls, they are used primarily to constrain the lateral movement of a debris flow, direct debris flow to travel along the desired path, and thereby protect an area of alluvial fan or structures on alluvial fan (Van Dine, 1996;Zhang et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%